An Interactive Web Application for Visualizing Climate Data. (28th May 2013) - Alder, J.; Hostetler, S.; Williams, D.
Abstract : Massive volumes of data are being created as modeling centers from around the world finalize their submission of climate simulations for the Coupled Model Intercomparison Project, phase 5 (CMIP5), in preparation for the forthcoming Intergovernmental Panel on Climate Change (IPCC) Fifth Assessment Report (AR5). Scientists, resource managers, and other potential users of climate data are faced with the daunting task of analyzing, distilling, and summarizing this unprecedented wealth of climate information.